Researching School Leadership through Ethnography: In Search for the Best Alternative - Tshabangu, Icarbord (International Journal of Asian Social Science, 2012)
Yukl (2009) has argued that defining and understanding leadership is not only arbitrary but subjective and laden with social influences. Researching social contexts such as schools and how school leaders exercise influence is a complex phenomena which may entail rejecting notions of generally seeking to use positivist approaches in educational research, as these may not meaningfully study human beings and their interactions. This paper examined the effectiveness of ethnography in educational research, particularly in school leadership. The study used empirical evidence from research activities conducted in Zimbabwe and Tanzania‟s secondary schools to advance a view that ethnography emerges as the best alternative to apprehend complex research activities where human interactions are central. This paper therefore explored some major features in ethnography with a view to illustrate how these are critical in establishing valid meanings and understanding and why these are relevant to studying school leadership. Some of these include multidisciplinary approach, insider status, immersion, listening and conversing. The Gadamerian hermeneutics to conversing and listening has been noted as a significant feature for ethnographers who seek to immerse themselves within studied communities so as to empathise and identify with studied communities. This study posits a view that despite a general trend by some educational researchers to seek to follow positivist approaches and by so doing claim to achieve validity, ethnography emerges as an effective approach particularly where social interactions such as in school leadership are under study.